2013
DOI: 10.1158/0008-5472.can-13-1753
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3B Upregulation and Genomic Mutation Patterns in Serous Ovarian Carcinoma

Abstract: Ovarian cancer is a clinically and molecularly heterogeneous disease. The driving forces behind this variability are unknown. Here we report wide variation in expression of the DNA cytosine deaminase APOBEC3B, with elevated expression in a majority of ovarian cancer cell lines (3 standard deviations above the mean of normal ovarian surface epithelial cells) and high grade primary ovarian cancers. APOBEC3B is active in the nucleus of several ovarian cancer cell lines and elicits a biochemical preference for dea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
181
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(198 citation statements)
references
References 40 publications
13
181
1
Order By: Relevance
“…The mechanistic details of these events following deamination by A3s remain uncharacterized, but working models have been proposed based upon what is known about AID-dependent SHM [5,[20][21][22]. As summarized in Figure 1, replication prior to removal of dU can result in C>T transitions due to incorporation of dA into the daughter strand through Watson-Crick base pairing.…”
Section: Deoxycytidine Deamination In Innate Immunity and Somatic Mutmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanistic details of these events following deamination by A3s remain uncharacterized, but working models have been proposed based upon what is known about AID-dependent SHM [5,[20][21][22]. As summarized in Figure 1, replication prior to removal of dU can result in C>T transitions due to incorporation of dA into the daughter strand through Watson-Crick base pairing.…”
Section: Deoxycytidine Deamination In Innate Immunity and Somatic Mutmentioning
confidence: 99%
“…This may be because epithelia are a front-line barrier to viruses, and hence the innate immune response, including A3 viral restriction, is more primed or active in these cells. A3B is highly expressed in tumor types with enrichment of A3 mutation signatures [37,38], and its expression correlates with prevalence of A3 signatures in breast and ovarian cancers [22,35]. Much attention therefore, has focused on A3B as an agent for genomic mutations.…”
Section: A3 Expression and Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical assays in vitro demonstrated that APO-BEC3B prefers substrate cytosines in 5"TCA and 5"TCG contexts. [9,11] Mutation data from three independent primary breast tumor genome datasets clearly indicated that mutations at these sites are significantly enriched. [9] Moreover, APOBEC3B expression levels correlated positively with both cytosine mutation and overall mutation loads.…”
Section: Apobec3b and Breast Cancermentioning
confidence: 99%
“…Some of these sources are well known, such as oxidation of guanine and hydrolytic deamination of cytosine, but many others are poorly defined. [3,8] However, much headway has been made recently in understanding additional endogenous sources of DNA damage, with our group [9][10][11][12] and others [2,3,13,14] implicating APOBEC3B, a member of the APOBEC family of single-stranded DNA (ssDNA) polynucleotide cytosine deaminases, in cancer genome mutagenesis [ Figure 1]. …”
mentioning
confidence: 99%